Ilmu Pegangan Hidup Seorang Muslim dalam Kesenian Kentrung Blora, Jawa Tengah - Firlie Ni'mah Husnayain; Sutiyono Sutiyono (Millah: Journal of Religious Studies, 2019)
Blora’s kentrung has changed as a performing arts so we can see its performance at big stage not only at small events. It becomes an art icon. The government strives for this art to remain sustainable, by bringing it up as an entertainment art for the people. Its educative values include the teaching of life philosophy in line with Walisongo teachings in a chronicle story supplemented with advice, prayer, and pantun in performances that entertain the audience. It is called "sipat rong puluh" or "the twenty character" in harmony with Javanese script which amounts to twenty. But there are two times the translation of "sipat rong puluh" with different explanations so that the number becomes forty points in the life philosophy, described as life philoshophy in particular for a Muslim. Because it is still closely related to Javanese beliefs that always maintain a balance between humans, God, and nature, it can also be applied in general to every human being to obtain a balanced life.